PREDICTION OF MOULD FILM THICKNESS IN THE BISMUTH BASED ALLOY CONTINUOUS CASTING PROCESS. Continuous casting is an important manufacturing process for producing ingots, slabs and flat products. The lubricant known as the mould flux in the meniscus region of continuous casting process flows through the space between the solidified shell and water cooled mould wall under the influence of the mould oscillation, gravity and the casting speed. The lubrication process in continuous casting upper mould - Barman Tambunan (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2006)
PREDICTION OF MOULD FILM THICKNESS IN THE BISMUTH BASED ALLOY CONTINUOUS CASTING PROCESS. Continuous casting is an important manufacturing process for producing ingots, slabs and flat products. The lubricant known as the mould flux in the meniscus region of continuous casting process flows through the space between the solidified shell and water cooled mould wall under the influence of the mould oscillation, gravity and the casting speed. The lubrication process in continuous casting upper mould region is characterized as the hydrodynamic lubrication phenomena. The film thickness at this working region zone is considered to be important and it may determine the quality of the surface of the billet/slab during continuous casting. Maintaining an optimal film thickness is very important to prevent the metal-to-metal contact between the surface of the strand and the mould wall. In this work, the changes in diameter of the cast bismuth based alloy billet were monitored during continuous casting in order to estimate the film thickness of the lubricant inside the mould. The result denotes that the thermal induced viscosity play an important role in the film thickness formation of a continuous casting process.